ДЕМОГРАФИЯЛЫҚ ӨСИЎГЕ ЭКОЛОГИЯЛЫҚ ФАКТОРДЫҢ ТӘСИРИ: МЕТОДОЛОГИЯЛЫҚ АСПЕКТЛЕРИ - Ниязимбетов, М.Қ. (FAN va JAMIYAT, 2021)
This article analyzes the factors influencing demographic growth. The methodological significance of the ecocentric paradigm in the “human-nature” system is revealed and the influence of this paradigm on demographic processes is based.